Information uncertainty and organizational design - Ferracuti, Elia (Journal of Accounting and Economics, 2022)
This paper investigates how information uncertainty, measured through variation in the informativeness of the public information environment, shapes the organizational design choices of firms. I posit that, when faced with higher uncertainty about demand and supply, managers are more likely to establish links to customer/supplier industries through high-level hiring decisions and vertical integration, thereby facilitating access to information about these industries. Consistent with this hypothesis, I find that firms modify their hiring and, to a lesser extent, vertical integration decisions in response to variation in the informativeness of the public information environment about demand and supply, measured with two distinct empirical approaches. Further, I observe that these organizational design choices correlate with the efficiency of inventory management and investment sensitivity to growth opportunities; this finding is consistent with organizational design facilitating access to information otherwise unavailable to managers through public sources.